Estimating some physiological parameters in the blood of Tilapia zillii fingerlings during adaptation to different salinities - Alkatrani, L.M.; Yesser, A.K.T.; Al-Adub, A.H.Y. (Mesopotamian Journal of Marine Sciences, 2022)
Two experiments were carried out on fingerlings of Tilapia zillii to estimate the effect of direct transfer from the control salinity of 15 psu to the different salinities of 1.5, 7.5, 15 and 30 psu during the periods of 6, 24, 48 and 96 hrs for short term effect experiments, and after 56 days for long term effect experiment in the salinities of 1.5, 7.5, 15 and 30 psu. Some physiological parameters (P.C.V.; osmolality; water content; Na+, K+ and Cl-, ions; glucose; total protein) were tested in the two experiments. Results of PCV showed a direct proportion with salinity increase, the time (96 hrs) was enough to reach the stable state of PCV. Fishes reach a new stable range of PCV in the salinities of 1.5, 7.5 and 15 psu after 56 days from transfer. Fishes seem hyperosmotic in the salinities of 1.5 and 7.5 psu and hyposmotic in the salinities of 15 and 30 psu. Plasma osmolality of the blood was significantly greater at 30 psu than the control salinity (15 psu), while it was significantly lower in the salinities of 1.5 and 7.5 psu at the time 96 hrs. Plasma osmolality decreased to values close to those of the three salinities 1.5, 7.5 and 15 psu at the time 56 days, indicating a strong osmoregulatory capacity of T. zillii fish. Water content in the muscles of T. zillii had inverse relationship with salinity increase in short term effect experiment. It was decreased significantly (P ≤ 0.05) at the time 56 days from other times in the short term effect experiment at salinities 1.5, 7.5 and 15 psu. Sodium and chloride ions concentrations had a direct proportion with salinity increase in the short term effect experiment. After 56 days from transfer, sodium and chloride ions concentrations reached a stable state and had close values at the three salinities (1.5, 7.5 and 15 psu), Potassium concentration values had a direct proportion with salinity increase and the values decreased with time at all salinities. However, the potassium concentration had a lower value in contrast to sodium and chloride ions. Glucose concentrations in the plasma of T. zillii had a direct proportion with salinity increase after 96 hrs transfer to different salinities (1.5, 7.5, 15 and 30 psu). The glucose of plasma decreased significantly (P ≤ 0.05) at all salinities (1.5, 7.5 and 15 psu) at the time 56 days compared to its levels at times of short term effect experiment. Protein concentration in the plasma decreased significantly (P ≤ 0.05) in the three salinities (1.5, 7.5 and 30 psu) compared with the control salinity (15 psu) at the time 96 hrs of short term effect experiment. After 56 days from transfer, plasma protein values in the three salinities (1.5, 7.5 and 15 psu) had a significant increase from other times in the short term effect experiment at all salinities. The results indicated that the salinity increase caused an increase in PCV, osmotic pressure, plasma ions, glucose, total protein; of T. zillii plasma and decrease in water content of muscles and fish seemed hyperosmotic in the salinities of 1.5, 7.5 psu and hyposmotic in the salinities of 15, 30 psu, also the time of 96 hrs was not enough for fish to reach the stable osmotic pressure at all salinities.